Scientific Evidence for the Updated Guidelines on Indications for Metabolic and Bariatric Surgery (IFSO/ASMBS) - De Luca, Maurizio; Shikora, Scott; Eisenberg, Dan; Angrisani, Luigi; Parmar, Chetan; Alqahtani, Aayed; Aminian, Ali; Aarts, Edo; Brown, Wendy; Cohen, Ricardo V.; Di Lorenzo, Nicola; Faria, Silvia L.; et al. (Springer Nature, 2025)
The 2022 American Society of Metabolic and Bariatric Surgery (ASMBS) and International Federation for the Surgery of Obesity and Metabolic Disorders (IFSO) updated the indications for Metabolic and Bariatric Surgery (MBS), replacing the previous guidelines established by the NIH over 30 years ago. The evidence supporting these updated guidelines has been strengthened to assist metabolic and bariatric surgeons, nutritionists, and other members of multidisciplinary teams, as well as patients. This study aims to assess the level of evidence and the strength of recommendations compared to the previously published criteria.